Genomic and Transcriptomic Analysis to Explore the Biological Characteristics of Cyclocybe chaxingu - Qiang Yang; Haiyan Song; Ge Su; Xuncheng Wang; Haijing Hu; Zhijun Zhai; Minghui Chen; Jianping Zhou; Hua Yin; Yang Gao; Dianming Hu (Horticulturae)
Cyclocybe chaxingu is an edible wood-decaying fungus widely cultivated in China, valued for its nutritional and economic significance. Despite its importance, molecular and genetic breeding studies on C. chaxingu have been limited by the lack of comprehensive genomic information. In this study, we performed whole-genome sequencing of the type strain JAUCC1847 of C. chaxingu for the first time and conducted extensive genomic and transcriptomic analyses. We assembled a high-quality genome of the C. chaxingu strain C27, with a total length of 50.79 Mb and a GC content of 50.90%. Comparative genomic analysis revealed a close evolutionary relationship with species from the genera Agrocybe and Stropharia, suggesting a recent common ancestor. The high ANI values between C. chaxingu, Agrocybe chaxingu, and Agrocybe cylindracea indicate a close phylogenetic relationship, raising the possibility of synonymy among these strains. Genome annotation identified a rich array of 573 carbohydrate-active enzymes, highlighting the metabolic diversity of C. chaxingu, particularly in lignocellulose degradation. Comprehensive analysis of the A and B mating-type locus in C. chaxingu revealed the distribution and structural characteristics of mating-type genes, providing crucial genetic information for further studies on the reproductive biology of this species. Transcriptomic analysis revealed distinct gene expression patterns in mycelia, stipe, and cap, reflecting their functional specialization. GO and KEGG enrichment analyses demonstrated the stipe’s association with structural integrity and transport, while the cap is linked to metabolic activity, gene regulation, stress responses, and DNA repair. These insights clarify the taxonomic status of C. chaxingu, supporting its recognition within the genus Cyclocybe and providing a valuable resource for future research and breeding programs.